HUBUNGAN ANTARA KETERAMPILAN METAKOGNITIF DAN RETENSI SISWA DALAM STRATEGI PEMBELAJARAN RECIPROCAL TEACHING DIPADU JIGSAW DIKELAS X SMAN 7 MALANG - Azizul Ghofar Candra Wicaksono; Aloysius Duran Corebima (Bioma : Jurnal Ilmiah Biologi, 2015)
This research was aimed to reveal the relationship betweenmetacognitive skill and retention in reciprocal teaching-jigsawstrategy.Metacognitive skill acted as predictor and retention asdependent variable. The learning process was held during onesemester and applied reciprocal teaching strategy combined withjigsaw. The subject of this research was 32 first years students in 7thstate senior high school of Malang. Instruments used in this researchwas essay test with metacognitive rubric to measure metacognitiveskill and essay test given in three weeks after the end of learningprocess to measure student?óÔé¼Ôäós retention. The research showed thatmetacognitive skill had a positive correlation with retention. Thus itcould be said that metacognitive skill is needed to improve student?óÔé¼Ôäósretention.Keywords: metacognitive skill, student retention, reciprocalteaching-jigsaw strategy